Development and investigation of the mathematical model for threedirectional forced synhronization system - Borsuk, Violeta; Rimas, Jonas (Lietuvos matematikos rinkinys, 2023)
Investigation of the threedirectional forced synhronization system, composed of four oscillators, is carried out. The exact expressions of the step responses functions for the synchronization system are derived and the transition process in the system is analysed.